Identifying factors influencing program selection in health sciences by underrepresented minority students—a scoping review - Mohammed, Sami Al Sufi; Roduta Roberts, Mary (Frontiers in Education, 2024)
There is a critical need to diversify health professionals in the provision of services to an increasing minority population in North America. Unfortunately, representation from minority groups in the health professions is lacking. Fewer underrepresented minority (URM) students choose a healthcare profession despite recruitment efforts made by government and academic institutions. Identifying the key factors for selecting a health sciences program by URM students may improve diversity in health science programs through admissions, thereby improving diversity in the future healthcare workforce and to explore underrepresented minority students' perceptions of facilitators and barriers that will or have influenced their decision to apply for health science programs. The Joanna Briggs Institute scoping review methodology was used to identify studies focusing on URM students' perceptions of facilitators and barriers to matriculate into a health science degree. Five electronic databases and gray literature were searched to identify North American papers published in-between 1942 to 2022. Twenty-one articles were analyzed. Following content analysis, the facilitators and barriers identified comprised personal, socioeconomic, educational, and financial. The most frequent facilitators reported were scholarships, family support, and the presence of role models. Common barriers included high tuition fees, preadmission criteria, lack of awareness about the health profession, availability of financial aid, and the admission process. The findings of this review will facilitate the development and implementation of customized, comprehensive strategies to recruit more URM students to health science programs in the future, thereby improving efforts toward creating a diverse healthcare workforce.